An Investigation of the Relationship Between the General Vaccination Attitudes of Pregnant Women and Their Attitudes Toward the COVID-19 Vaccine - Mamuk, Rojjin; Akgün, Meryem; MİRAL, MUKADDES TURAN; Göksu, Şerife (Routledge, 2023)
This study aimed to investigate the relationship between the attitudes of pregnant women toward general vaccines based on the Health Belief Model and their attitudes toward the COVID-19 vaccine. The study, which was designed as a descriptive, cross-sectional, and correlational study, was conducted with 348 pregnant women in three public hospitals in Northern Cyprus between June 24 and November 28, 2022. Data were collected using the “Participant Information Form,” “Public Attitude Toward Vaccination Scale-Health Belief Model” (PAVS-HBM), and “Attitudes Toward the COVID-19 Vaccine” (ATV-COVID-19). The COVID-19 vaccination rate among pregnant women was quite high. Pregnant women have a high perception of sensitivity, importance, benefit, and health responsibility for routine vaccines and vaccination programs based on the HBM, and a low perception of barriers to vaccination. These results showed that pregnant women have a determined and positive attitude toward the acceptance of vaccines in general. On the other hand, the attitude of pregnant women toward the COVID-19 vaccine was moderately negative. Despite the reservations about the COVID-19 vaccine, a determined and positive attitude toward vaccines in general has increased acceptance of the COVID-19 vaccine.
Keywords: Attitude; Covid-19 Vaccines; Health Belief Model; Pandemic; Pregnancy; Vaccines